https://scholarworks.wmich.edu/cgi/viewcontent.cgi?article=1299&context=jcp - Stephen A. Klien; John Elmer; Patrick J. Rottinghaus (Central States Communication Association, 2024)
Helping students make connections between the disciplinary study of communication and the development of student agency in career exploration can be an important part of the mission of the introductory course in communication. This study incorporates social cognitive career theory to examine the effects of a semester-long communication career awareness research project as an intervention in an introductory communication course at a large public university in the Midwest. Survey data from 83 undergraduate students were analyzed to measure perceptions of self-efficacy, perceived competence, autonomy support, and adaptability for career exploration. The results of paired samples t-tests found significant gains on all four dependent variables. These findings indicate the potential for such a project in introductory courses to promote career exploration agency.